Learning AutoCAD Electrical 2015 - Bryant, Shaun (InfiniteSkills, 2014)
"In this AutoCAD Electrical 2015 training course, expert author Shaun Bryant teaches you the tools and techniques you need to create electrical CAD designs. This course is designed for the absolute beginner, meaning no prior experience with AutoCAD is required. You will start by touring the AutoCAD interface and learning about the various drafting settings. Once you've covered the basics and have set up your project, Shaun takes you through the electrical drawing process. You will learn to insert wires, ladders, and components, covering each topic in detail. Shaun will teach you how to edit components, insert connectors, and add footprints from the icon menu. This video tutorial will also cover topics including PLC modules, terminals and creating and editing symbols. Finally, you will learn about project and drawing properties, and how to plot the project. Once you have completed this computer based training course, you will have gained a comprehensive understanding of the tools and techniques in AutoCAD, and be able to apply them to your own electrical design projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.